Reconstruction Of The Legal Relations Of The Central And Local Governments In Handling The Pandemic In Indonesia - Rahardiansah, Trubus; Wahid, Eriyantouw; M. Asror, Endyk (Journal of World Science, 2022)
In 2020, a health emergency became a condition that affected the stability of the Indonesian state, especially in certain areas that require proper and prompt handling. The Covid-19 virus outbreak (also known as the coronavirus), has infected millions of people across Indonesia. The legal basis used to draft the handling policy, at least also based on the 1945 NRI Constitution, Law No. 24 of 2007 on Disaster Management (hereinafter referred to as Law No. 24 of 2007) and Law No. 6 of 2018 on Health Quarantine (hereinafter referred to as Law No. 6 of 2018). The issue raised is how the implementation of law enforcement and legal sanctions in handling the Covid-19 pandemic in Indonesia based on Law No.6 of 2018 concerning Health Quarantine and reconstruction of legal relations between the central and local governments in handling the pandemic effectively in Indonesia? The method used is normative legal research methods. Normative legal research itself is a research method that examines the law from an internal perspective with the object of research is the legal norm. The approaches used in this study are the statute approach and the conceptual approach. This research is based on the regulation of laws and regulations governing the handling and management of the Covid-19 pandemic and analysis of the concept of determining the laws and regulations. The conclusions that can be drawn include a comprehensive analysis of the substance of Law No. 24 of 2007, Law No. 6 of 2018, and Law No. 23 of 2014 shows the unclear legal relationship between the central government and local governments in emergency situations (extraordinary), especially in handling the pandemic. As a result, its implementation often causes legal conflicts between the central and local governments that hinder the handling of Covid-19 in Indonesia. The Regional Government, on the basis of autonomy has the right to take care of its regional affairs, including in dealing with problems that occur in the region. The results of this study provide advice and recommendations including The Need for Synchronization and Harmonization of the Regulation of Law No.24 of 2007 on Disaster Management, Law No.23 of 2014 on Local Government and Law No.6 of 2018 on Health Quarantine so that the construction of central and regional legal relations in handling outbreaks in Indonesia can be more responsive and effective in its implementation